2012
DOI: 10.1111/j.1574-695x.2011.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression profiling ofEhrlichia ruminantiumat different stages of development

Abstract: Ehrlichia ruminantium (ER), the causative agent of heartwater on ruminants, is an obligate intracellular bacterium transmitted by ticks of the genus Amblyomma. Previous studies have shown that early stages of development may be critical for Ehrlichia pathogenicity. To gain insights into the biology of intracellular ER, we determined the genome-wide transcriptional profile of ER replicating inside bovine aortic endothelial cells using DNA microarrays. At intermediate and late stages of infection (reticulate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 21 publications
6
33
1
1
Order By: Relevance
“…Transcriptional profiling comparing the equivalent intracellular ("RB") versus infectious ("EB") forms in Ehrlichia ruminatum also found that an APH_1235 ortholog, CDS_00640, was upregulated in the infectious EB form (30). Further evidence of the development of the DC form is provided by the detection of multiple chaperones and stress response proteins (see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 90%
“…Transcriptional profiling comparing the equivalent intracellular ("RB") versus infectious ("EB") forms in Ehrlichia ruminatum also found that an APH_1235 ortholog, CDS_00640, was upregulated in the infectious EB form (30). Further evidence of the development of the DC form is provided by the detection of multiple chaperones and stress response proteins (see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 90%
“…Bacterial replication itself needs nutrients from the host and occurs thanks to the subversion of host cell machineries (e.g., manipulation of autophagy or cholesterol pathways; Barnewall et al, 1997; Niu et al, 2008; Xiong et al, 2008; Wakeel et al, 2009; Liu et al, 2012; Xiong and Rikihisa, 2012). Recent transcriptomic studies on E. ruminantium infectious form provide evidence of the expression of genes involved in the bacterial defense and invasion systems, showing that Ehrlichia allocates a significant part of its energetic resources to virulent purposes (Pruneau et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to investigate the global gene expression analysis of E. ruminantium Welgevonden in different developmental stages using transcriptome or RNA-sequencing. Available studies are based on microarray analysis (Emboulé et al, 2009;Pruneau et al, 2012). In general, microarray results are consistent with RNA-seq data, but the RNA-seq technique is more sensitive (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 88%